Language and social competence in typically developing children and late talkers between 18 and 35 months of age. Issue 3 (3rd March 2016) - Longobardi, Emiddia; Spataro, Pietro; Frigerio, Alessandra; Rescorla, Leslie
Abstract : The present study examined the relation between language and social ability in a sample of 268 preschoolers aged 18–35 months. Expressive language was assessed with the Italian adaptation of the Language Development Survey (LDS), and Social Competence was assessed with the Questionnaire on Peer Interactions in the Kindergarten (QPI). Results showed that language measures (LDS Vocabulary, LDS MLU and the opportunity scores of the LDS category of People Words) predicted social competence (Total QPI score and the standardised scores of the 'Popularity', 'Prosociality', 'Aggressiveness', 'Adult Dependence', and 'Isolation' factors), above and beyond the proportion of variance explained by age. In addition, children with delayed language development (who were older than 24 months and produced fewer than 50 words) exhibited lower social abilities, compared to age-matched children. These findings support the conclusion that language skills play a critical role for social adjustment.